Two customers purchased coffee and doughnuts at a coffee shop. Each cup of coffee costs the same amount, and each doughnut costs the same amount. The system of equations below can be used to find c, the cost of a cup of coffee, and d, the cost of a doughnut.

x+2d4.90 2x+ 3x 8.60
What is the cost of 1 cup of coffee?
$4.90
$2.50
$3.70
$1.20

1 answer

The system of equations appears to be missing some equality signs and is somewhat unclear. Based on what I interpret from your message, it seems there are two customers who made two transactions that we can represent as follows:

  1. The first customer's total cost is for \( x \) cups of coffee and \( 2 \) doughnuts: \[ x + 2d = 4.90 \]

  2. The second customer's total cost is for \( 2x \) cups of coffee and \( 3 \) doughnuts: \[ 2x + 3d = 8.60 \]

Now we can solve this system of equations for \( c \) (the cost of one cup of coffee) and \( d \) (the cost of one doughnut).

Step 1: Rearranging the equations

  • From the first equation, we have: \[ x + 2d = 4.90 \quad \text{(1)} \]

  • From the second equation, we have: \[ 2x + 3d = 8.60 \quad \text{(2)} \]

Step 2: Solve for \( x \) in terms of \( d \) using equation (1) \[ x = 4.90 - 2d \quad \text{(3)} \]

Step 3: Substitute equation (3) into equation (2) Now substitute \( x \) from equation (3) into equation (2): \[ 2(4.90 - 2d) + 3d = 8.60 \] Expanding this, \[ 9.80 - 4d + 3d = 8.60 \] Combine like terms: \[ 9.80 - d = 8.60 \] Now isolate \( d \): \[ -d = 8.60 - 9.80 \] \[ -d = -1.20 \] \[ d = 1.20 \]

Step 4: Substitute \( d \) back into equation (3) to find \( x \) Now use \( d = 1.20 \) in equation (3): \[ x = 4.90 - 2(1.20) \] Calculate \( x \): \[ x = 4.90 - 2.40 = 2.50 \]

Now we have the quantities:

  • \( x = 2.50 \) (the cost of one cup of coffee)

Answer: The cost of 1 cup of coffee is $2.50.